Public Art Practices in Urban Space: The Case of Istanbul - Kucukali, Ufuk Fatih (Street Art & Urban Creativity, 2023)
In addition to revealing the relationship of public art with the city, which is the intersection of space and human life, the relationship between public space and art has been researched, the concept of public art has been examined, and its development processes in the world and in Turkey have been emphasized. The social, cultural, economic and physical effects of public art on the city were investigated. The relations between the effects of public art on the space and the city were questioned and evaluated with the examples examined within the scope of the article. An approach to researching and examining the resulting relationships and the effects of public art on urban spaces is presented, and the relationship of public art with a city with historical sites such as Istanbul is presented.